2016
DOI: 10.1177/0885066616682232
|View full text |Cite
|
Sign up to set email alerts
|

Role of B-Type Natriuretic Peptide in Predicting In-Hospital Outcomes in Acute Exacerbation of Chronic Obstructive Pulmonary Disease With Preserved Left Ventricular Function: A 5-Year Retrospective Analysis

Abstract: Elevated admission BNP in patients with AECOPD and normal LVEF is associated with worse in-hospital outcomes and can be used to risk-stratify these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
1
13
0
1
Order By: Relevance
“…25,33,35 Disease severity was also identified as a driver of ED visits, 35 and longer hospital or ICU stays. 38 These multivariate data support trends reported in other studies, captured both in this SLR and others in the broader literature. As an example, a cross-sectional survey conducted across France, Germany, Italy, Spain and the UK found that moderate-to-severe dyspnea was associated with a significant disease burden in patients with COPD, and was associated with significantly more frequent hospitalizations, specialist and physician consultations, LTOT use and pulmonary rehabilitation (all p<0.0001).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…25,33,35 Disease severity was also identified as a driver of ED visits, 35 and longer hospital or ICU stays. 38 These multivariate data support trends reported in other studies, captured both in this SLR and others in the broader literature. As an example, a cross-sectional survey conducted across France, Germany, Italy, Spain and the UK found that moderate-to-severe dyspnea was associated with a significant disease burden in patients with COPD, and was associated with significantly more frequent hospitalizations, specialist and physician consultations, LTOT use and pulmonary rehabilitation (all p<0.0001).…”
Section: Discussionsupporting
confidence: 89%
“…25 Factors independently associated with longer hospital stays for a COPD exacerbation were numerous and were reported in six studies. 31,32,[36][37][38][39] Drivers included the presence of comorbidities such as stroke 31 and some cardiac abnormalities, 31,32 advancing age and being female. 36 Furthermore, specific care-related factors such as a hospital's size, location or type were also found to be independent drivers of length of stay.…”
Section: Hrumentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary pathology such as acute respiratory distress syndrome and chronic obstructive pulmonary disease and interventions such as mechanical ventilation influence the BNP levels in this population. 21,30 As noted in this metaanalysis, studies variably exclude preexisting chronic kidney disease and inconsistently adjust for acute kidney injury in their analyses. In patients with sepsis, studies have found conflicting results regarding correlations between BNP and serum creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…15 In other critically ill patients with pulmonary embolism, chronic obstructive pulmonary disease, and congestive heart failure, BNP has been strongly associated with clinical outcomes and has been incorporated into risk stratification. [19][20][21] In patients with sepsis, however, there are conflicting data on the role of BNP/NT-proBNP as a risk-stratification and prognostication tool. Some investigators have considered BNP as a marker of severity, whereas others have reported it as an independent prognostic test.…”
mentioning
confidence: 99%